Next-Generation Low-Latency Architectures for Real-Time AI-Driven Cloud Services - Sandeep Konakanchi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The rapid evolution of AI-driven applications has created a pressing demand for next-generation low-latency cloud architectures capable of delivering real-time performance. This article explores innovative architectural designs and technologies that push the boundaries of traditional cloud systems to meet the stringent requirements of latency-sensitive AI services. A holistic framework that minimizes latency while maximizing processing efficiency and scalability by integrating edge computing, distributed data processing, adaptive load balancing, and dynamic scaling. The article focuses on optimizing data flow across hybrid cloud environments, enabling AI models to make instant predictions and decisions without compromising accuracy or reliability. This pioneering exploration also addresses challenges such as data synchronization, resource contention, and network bottlenecks, offering novel solutions to create robust, AI-powered cloud services tailored for real-time use cases across critical sectors, including healthcare, finance, and autonomous systems.